Use of telehealth and outcomes before a visit to the emergency department: a cross-sectional study on walk-in patients in Switzerland (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY An increasing number of patients are using telehealth before contacting the healthcare system. If we are to optimise future telehealth strategies and adequately respond to patient needs, we need to know more about the frequency and characteristics of telehealth use. Our objectives were (i) to investigate whether patients use telehealth before consulting the emergency department (ED), (ii) to compare patients with and without use of telehealth, and (iii) to investigate adherence, confidence and satisfaction. MATERIALS AND METHODS A survey was conducted among ED walk-in patients at a tertiary university hospital in Switzerland. Eligible patients were questioned about their use of telehealth before current presentation, during 30 shifts from 23 October to 15 December 2019. RESULTS A total of 183 (43.9%) of 417 surveyed patients used telehealth, with the telephone being the most commonly used modality, especially among elderly patients. Patients using telehealth were more likely to be male (53.5%, p = 0.001) and were similar in age to non-users. Telehealth users tended to be better educated. Telehealth was predominantly used for semi-urgent non-traumatic diseases that did not lead to hospitalisation. All age groups expressed satisfaction with telehealth, trusted the recommendations and adhered to them. The main reason for "non-use" of telehealth was lack of knowledge. CONCLUSIONS Lack of knowledge about telehealth opportunities and barriers in specific patient groups should be addressed to include all patients, and thus to exploit telehealth’s many advantages.